School cultures, transformational leadership and students’ academic achievement - Daud, Yaakub; Don, Yahya (Universiti Utara Malaysia Press, 2012)
Purpose – School culture and school leadership potentially contribute to students’ academic achievement, and teachers’ satisfaction and productivity.The aim of this study was to identify the relationship between school culture, transformational leadership, and academic achievement among primary school's students. Methodology – This correlational study involved 657 teachers and 141 headmasters from 141 primary schools in Kedah. The School Culture Inventory (SCI) and The Multi factor Leadership Questionnaire were used as survey instruments.Structured interviews which involved 16 teachers and four headmasters were also used to identify positive values that were practiced in school.Findings – The analysis found a significant difference in perceptions of school culture among teachers in high performance schools and teachers in low performance schools.It was also found that school culture had a positive and significant relationship with transformational leadership.Significance – The study indicated that school culture and transformational leadership relates strongly with students’ academic achievement.Thus a positive school culture and transformational leadership are expected to contribute to the success of a school.